DEVELOPMENT, OPTIMISATION AND THE ORGANOLEPTIC PROPERTIES OF EXTRUDED SORGHUM-BASED GLUTEN-FREE PASTA - Chopera, Prosper; Gwekwe, Blessing; Matsungo, Tonderayi M; Nyanga, Loveness K; Chidewe, Cathrine; Mukanganyama, Stanley; Nyakudya, Elijah; Mtambanengwe, Florence; Mapfumo, Paul (Food and Feed Research, 2024)
Pasta is one of the most consumed staples worldwide.  New formulations incorporating novel nutritious ingredients are now common in its production. The purpose of this study was to formulate, optimise and evaluate the organoleptic properties of a sorghum based extruded gluten free pasta. Sorghum flour, pearl millet flour, high iron bean flour (Biofortified NUA 45 beans) and Hermes potato flour were evaluated for proximate and micronutrient composition, formulated to produce pasta through extrusion process. Three sorghum-based pastas namely sorghum high bean pasta (Treatment SHBP), sorghum bean pasta (Treatment SBP) and sorghum high potato pasta (Treatment SHPP) were produced and evaluated for sensorial properties (visual, palpatory and gustatory qualities). The Box Benhken Design (BBD) in conjunction with Response Surface Methodology (RSM) was used to select the best formulation by evaluating cooking quality parameters and organoleptic parameters. The protein content in the four flours ranged from 10.52% to 22%. NUA 45 bean flour had significantly (p
Keywords: Gluten free pasta, Sorghum extrusion, organoleptic properties, cooking properties